The Impact of Being a Public Organization on the Public's Perceptions of the Florida Forest Service's Brand - Quisto Settle; Joy Rumble; Ricky Telg; Traci Irani; Hannah Carter; Allen Wysocki (Journal of Applied Communications, 2015)
The purpose of this study was to address how being a public organization affected the public’s perceptions of the Florida Forest Service’s brand. Focus groups were conducted at different sites across the state with rural and urban residents. The major findings were that the public expected the brand of a public organization to be financially responsible (e.g., justify the purpose of the organization, avoid duplication between public organizations, communicating with the public without wasting money, and generating revenue), provide something valuable to individuals or the public at large (e.g., protecting forests, control through regulations, and aid, such as providing information), and to operate with integrity (e.g., being financially responsibly, communicating clearly with the public, and the organization being fair in balancing public and private interests). This research addresses a gap in research regarding the branding of public organizations. Because the study is limited by being a qualitative study addressing one organization in one state, future research should be conducted to address the transferability of the findings to other settings. This research furthers efforts to foster relationships between public organizations and members of the public by providing guidance for the improvement of the brands of public organizations. In the face of increased scrutiny of and competition between public organizations, the findings of this study can be used to help improve the public’s perceptions of public organizations.
Keywords: Brand; public organization; forestry; focus groups